Metal organic framework material as well as preparation method and application thereof

By using the metal organic frame material coordinated by malic acid and 4,4'-bipyridine as adsorbent, the separation problem of acetylene and carbon dioxide mixture was solved, and acetylene purification with high purity and high yield was achieved, with good economic benefits and industrial application potential.

CN119798701AActive Publication Date: 2025-04-11NANCHANG UNIV

Patent Information

Application Number
CN202510085836.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-11
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove mixtures of acetylene and carbon dioxide, especially in the high purity and high yield requirements of acetylene, and traditional methods such as low temperature distillation or solvent extraction have huge costs and energy consumption problems.

Method used

Metal organic frame materials (MOFs) formed by malic acid as the organic ligand and 4,4'-bipyridine as the column support and transition metal nodes are used as adsorbents to form a frame surface environment with a high-density pore cage structure and a strong negative electrostatic potential through self-assembly and coordinated positioning to achieve efficient separation of acetylene and carbon dioxide.

Benefits of technology

It has achieved high purity and high yield purification of acetylene from carbon dioxide, with super strong capture effect and large storage space, has excellent separation effect on acetylene/carbon dioxide mixed system, and has good economic benefits and industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798701A_ABST
    Figure CN119798701A_ABST
Patent Text Reader

Abstract

The invention discloses a metal organic framework material as well as a preparation method and application thereof, and belongs to the technical field of chemical separation. The preparation method of the metal organic framework material provided by the invention comprises the following steps: taking water and methanol as solvents, taking 4, 4 '-dipyridyl and malic acid as organic ligands, adding a zinc source, reacting, and in the reaction process, connecting oxygen atoms on the malic acid with zinc ion bonds on the zinc source to form a 2D layered network structure, the two-dimensional layered network structures are bridged through 4, 4 '-dipyridyl to form a 3D rigid network framework, and after the reaction is finished, the metal organic framework material is prepared. The metal organic framework prepared by the invention has a superstrong capture effect and a large storage space on acetylene molecules, and also has an excellent separation effect on an acetylene and carbon dioxide mixed system, so that the aim of purifying acetylene in the acetylene and carbon dioxide mixture at high purity and high yield is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical separation, and more specifically to a metal organic framework material and a preparation method and application thereof. Background Art

[0002] In recent years, with the efficient use of natural gas and coal resources, acetylene (C2H2) has been transformed from being used as a fuel to a high-value raw material for the production of various organic chemicals and polymers. In its production process, carbon dioxide (CO2) will inevitably coexist with it as an impurity, ranging from 3% to 50%, which poses a challenge to its subsequent industrial utilization efficiency. In order to produce high-purity (>99%) C2H2, the removal of CO2 is very necessary. However, due to the same kinetic molecular size of the two molecules Similar physical properties (boiling points: C2H2, 189.3K; CO2, 194.7K) make C2H2 / CO2 separation one of the most difficult and challenging chemical separation processes. Traditional methods that rely on low-temperature distillation or solvent extraction usually require huge costs and energy consumption. In order to solve this problem, the adsorption separation and technology using advanced adsorbents have outstanding advantages such as low energy consumption, high product purity, simple process flow, and small scale-up effect, and have good industrial application prospects.

[0003] Traditional porous adsorbents such as zeolite molecular sieves and activated carbon usually have low adsorption capacity and selectivity, making it difficult to reach the level of industrial application. As emerging crystalline porous materials, metal organic frameworks (MOFs) or porous coordination polymers (PCPs) have obvious advantages in the separation of light hydrocarbon mixtures. In principle, an ideal C2H2 / CO2 separation adsorbent should have high adsorption capacity, selectivity and moderate adsorption heat. In addition, industrial parameters such as stability, cost-effectiveness and scalability are all relatively important parameters. At present, in metal organic frameworks for the separation of C2H2 / CO2 mixtures, the trade-off between adsorption capacity and separation selectivity, economic benefits and the realization of large-scale industrial production are still common problems. Therefore, finding efficient adsorbents suitable for industrial applications remains a challenge. Summary of the invention

[0004] In view of the above problems, the present invention provides a metal organic framework material and its preparation method and application. Using cheap and widely available malic acid as an organic ligand and 4,4'-bipyridine as a pillar, it coordinates with transition metal nodes to participate in the architecture, and self-assembles to form a metal organic framework (MOFs) adsorbent with a high-density pore cage structure and a framework surface environment with a strong negative electrostatic potential. The metal organic framework can be scaled up for synthesis and large-scale industrial production. The prepared metal organic framework has a super strong capture effect and large storage space for acetylene molecules, and also has an excellent separation effect on the acetylene carbon dioxide mixed system, achieving the purpose of purifying acetylene with high purity and high yield in the acetylene carbon dioxide mixture. In addition, the low synthesis cost and the synthesis method that can be synthesized in large quantities make it likely to become a preferred adsorbent for actual industrial pressure swing adsorption applications.

[0005] The first object of the present invention is to provide a method for preparing a metal organic framework material, comprising the following steps:

[0006] Using water and methanol as solvents, 4,4'-bipyridine and malic acid as organic ligands, and adding a zinc source, the reaction is carried out. During the reaction, the oxygen atoms on the malic acid are bonded to the zinc ions on the zinc source to form a 2D layered network structure. The 2D layered network structure is bridged by 4,4'-bipyridine to form a 3D rigid network framework. After the reaction is completed, a metal organic framework material is prepared. The cavity size of the 3D rigid network framework is 0.85×0.6×0.62nm 3 The pore size connecting adjacent cavities is 0.3nm×0.39nm, and the pore capacity is 0.1~0.2cm 3 / g, porosity of 30-40%, specific surface area of ​​150-300m 2 / g.

[0007] In a preferred embodiment of the present invention, the molar ratio of the zinc source to 4,4'-bipyridine is 4 to 5:3, for example, the molar ratio of the zinc source to 4,4'-bipyridine is 4:3, 4.2:3, 4.4:3, 4.6:3, 4.8:3, 5:3, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0008] In a preferred embodiment of the present invention, the molar ratio of 4,4'-bipyridine to malic acid is 4:3-4, for example, the molar ratio of 4,4'-bipyridine to malic acid is 4:3, 4:3.2, 4:3.4, 4:3.6, 4:3.8, 4:4, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0009] In a preferred embodiment of the present invention, the reaction temperature is 120°C to 150°C, and the reaction time is 40h to 48h. For example, the reaction temperature is 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc., and the reaction time is 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h, 48h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0010] In a preferred embodiment of the present invention, the volume ratio of water to methanol is 1:1-2, for example, the volume ratio of water to methanol is 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2.

[0011] The ratio of zinc source to water is 2.4mmol to 3mmol:5ml. For example, the ratio of zinc source to water is 2.4mmol:5ml, 2.5mmol:5ml, 2.6mmol:5ml, 2.7mmol:5ml, 2.8mmol:5ml, 2.9mmol:5ml, 3mmol:5ml, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable.

[0012] The second object of the present invention is to provide a metal organic framework material prepared by the above preparation method.

[0013] The third object of the present invention is to provide the use of the above metal organic framework material as an adsorbent, wherein the metal organic framework material is used as an adsorbent and is contacted with a gas mixture containing acetylene and carbon dioxide to perform adsorption separation.

[0014] In a preferred embodiment of the present invention, in the gas mixture, the volume percentage of acetylene is 1% to 99%, and the rest is carbon dioxide, wherein the volume percentage of acetylene is 1%, 11%, 21%, 31%, 41%, 51%, 61%, 71%, 81%, 91%, 99%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, the temperature of adsorption separation is -50°C to 100°C, and the adsorption pressure is 0 bar to 10 bar. For example, the temperature of adsorption separation is -50°C, 0°C, 50°C, 100°C, etc., and the adsorption pressure is 0 bar, 1 bar, 2 bar, 3 bar, 4 bar, 5 bar, 6 bar, 7 bar, 8 bar, 9 bar, 10 bar, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the contacting method is any one of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention uses cheap and widely available malic acid as an organic ligand, 4,4'-bipyridine as a pillar, and coordinates with transition metal nodes to participate in the framework, and self-assembles to form a metal organic framework material (MOFs) adsorbent with a high-density pore cage structure and a framework surface environment with a strong negative electrostatic potential. It has a super strong capture effect and a large storage space for acetylene molecules, and also has an excellent separation effect on the acetylene carbon dioxide mixed system, achieving the purpose of purifying high-purity acetylene from carbon dioxide. The metal organic framework material constructed by the present invention has a dense pore cage structure, which provides a larger space for gas storage. At the same time, a large number of negatively charged oxygen atoms are distributed on the surface of the pore cage, which has a strong affinity with the positively charged hydrogen atoms at both ends of the acetylene molecule, and repel the negatively charged oxygen atoms at both ends of the carbon dioxide molecule, thereby achieving a high separation selectivity for acetylene / carbon dioxide.

[0019] (2) The metal organic framework material prepared by the present invention has the advantages of high efficiency in capturing acetylene from the acetylene and carbon dioxide mixed components, excellent dynamic breakthrough performance stability, material recycling renewability and solvent stability, good thermal stability, and considerable economic benefits.

[0020] (3) The metal organic framework material prepared by the present invention realizes the transformation from gram-level synthesis to kilogram-level synthesis through the optimization of synthesis conditions. At the same time, the kilogram-level synthesized sample still maintains excellent adsorption performance for C2H2 / CO2 mixed gas, excellent dynamic breakthrough performance stability, material recycling renewability and solvent stability, good thermal stability, and considerable economic benefits, making it promising as a potential physical adsorbent in the field of industrial adsorption and separation technology such as high-efficiency and low-energy pressure swing adsorption, realizing the replacement of traditional energy-intensive technologies in industry such as solvent extraction or low-temperature distillation for separating acetylene and carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical picture of the Zn-bpy-DLmal material prepared in Example 1 of the present invention.

[0022] Figure 2 This is a physical picture of the enlarged synthesis of the Zn-bpy-DLmal material prepared in Example 1 of the present invention.

[0023] Figure 3 This is the process route diagram of the Zn-bpy-DLmal material prepared in Example 1 of the present invention.

[0024] Figure 4 This is a physical picture of the Zn-bpy-fum material prepared in Comparative Example 1 of the present invention.

[0025] Figure 5 This is a structural diagram of the Zn-bpy-DLmal material prepared in Example 1 of the present invention, wherein a is a three-dimensional structural diagram, b is a YZ plane structural diagram, and c is an XZ plane structural diagram.

[0026] Figure 6 This is a structural diagram of the Zn-bpy-fum material prepared in Comparative Example 1 of the present invention, wherein a is an XZ plane structural diagram and b is an XY plane structural diagram.

[0027] Figure 7 1 is the X-ray diffraction pattern of the Zn-bpy-DLmal material prepared in Example 1 of the present invention, wherein a is a comparison diagram of the X-ray diffraction patterns of the Zn-bpy-DLmal material in different states, and b is an X-ray diffraction pattern after immersion in different organic solutions.

[0028] Figure 8 This is a thermogravimetric curve of the Zn-bpy-DLmal material prepared in Example 1 of the present invention.

[0029] Fig. 9 This is the CO2 adsorption isotherm of the Zn-bpy-DLmal material prepared in Example 1 of the present invention at 195K, wherein the inset is the BET diagram of the Zn-bpy-DLmal material prepared in Example 1.

[0030] Fig.10 This is the CO2 adsorption isotherm of the Zn-bpy-fum material prepared in Comparative Example 1 of the present invention at 195K, wherein the inset is the BET diagram of the Zn-bpy-DLmal material prepared in Comparative Example 1.

[0031] Fig.11 This is the adsorption isotherm of acetylene and carbon dioxide of the Zn-bpy-DLmal material prepared in Example 1 of the present invention at 298K.

[0032] Fig.12 This is the adsorption isotherm of acetylene and carbon dioxide at 298K for the Zn-bpy-fum material prepared in Comparative Example 1 of the present invention.

[0033] Fig.13 This is the kinetic adsorption curve of the acetylene and carbon dioxide adsorption amount of the Zn-bpy-DLmal material prepared in Example 1 of the present invention at 298K as a function of time and pressure.

[0034] Fig.14Dynamic penetration curves of acetylene / carbon dioxide mixed gas components at different flow rates at 298K for the Zn-bpy-DLmal material prepared in Example 1 of the present invention.

[0035] Fig.15 This is the cyclic dynamic breakthrough curve of the acetylene / carbon dioxide mixed gas components of the Zn-bpy-DLmal material prepared in Example 1 of the present invention at 298K.

[0036] Fig.16 This is the acetylene desorption process curve of the Zn-bpy-DLmal material prepared in Example 3 of the present invention after dynamic penetration of the acetylene / carbon dioxide mixed gas components at 298K.

[0037] Fig.17 This is the adsorption isotherm of acetylene and carbon dioxide at 298K for a kilogram-scale synthetic sample of the Zn-bpy-DLmal material prepared in Example 3 of the present invention.

[0038] Fig.18 Dynamic penetration curve of acetylene / carbon dioxide mixed gas components (volume ratio 1:1, flow rate 2.0 mL / min) at 298K for a kilogram-scale synthetic sample of the Zn-bpy-DLmal material prepared in Example 3 of the present invention.

[0039] Fig.19 This is the dynamic penetration curve of the acetylene / carbon dioxide mixed gas components of the Zn-bpy-fum material prepared in Comparative Example 1 of the present invention at 298K.

[0040] Fig. 20 This is the acetylene desorption process curve of the Zn-bpy-fum material prepared in Comparative Example 1 of the present invention after dynamic penetration of the acetylene / carbon dioxide mixed gas components at 298K. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] A method for preparing a metal organic framework material comprises the following steps:

[0044] Dissolve 2.4mmol zinc acetate dihydrate in 5mL ultrapure water, 1.8mmol 4,4'-bipyridine and 1.8mmol DL-malic acid in 5mL methanol, transfer the two mixed solutions to a polytetrafluoroethylene reactor after they are fully dissolved, stir at room temperature for 1h to fully mix, then place in a 140℃ oven to react for 48h, and cool to room temperature 10h after the reaction. The obtained white crystal sample is the Zn-bpy-DLmal crystal sample, as shown in the actual picture Figure 1 shown.

[0045] Example 2

[0046] A method for preparing a metal organic framework material comprises the following steps:

[0047] 24mmol zinc acetate dihydrate was dissolved in 50mL ultrapure water, 18mmol 4,4'-bipyridine and 18mmol malic acid were dissolved in 50mL methanol, and after being fully dissolved, the two mixed solutions were stirred at room temperature for 1h to be fully mixed, and stirred and refluxed at 120°C for 48h. The obtained slurry was collected by suction filtration, and the obtained solid was dried at 60°C to obtain the Zn-bpy-DLmal powder sample.

[0048] Example 3

[0049] A method for preparing a metal organic framework material comprises the following steps:

[0050] Dissolve 240mmol zinc acetate dihydrate in 500mL ultrapure water, 180mmol 4,4'-bipyridine and 180mmol malic acid in 500mL methanol, stir the two mixed solutions at room temperature for 1h to mix them evenly, and stir and reflux at 120℃ for 48h. The obtained slurry is collected by suction filtration, and the obtained solid is dried at 60℃ to obtain the Zn-bpy-DLmal powder sample. Figure 2 As shown, the preparation process is as Figure 3 shown.

[0051] Example 4

[0052] A method for preparing a metal organic framework material comprises the following steps:

[0053] 30mmol zinc acetate dihydrate was dissolved in 50mL ultrapure water, 18mmol 4,4'-bipyridine and 18mmol malic acid were dissolved in 100mL methanol, and after being fully dissolved, the two mixed solutions were stirred at room temperature for 1h to be fully mixed, and stirred and refluxed at 150°C for 40h. The obtained slurry was collected by suction filtration, and the obtained solid was dried at 60°C to obtain the Zn-bpy-DLmal powder sample.

[0054] Example 5

[0055] A method for preparing a metal organic framework material comprises the following steps:

[0056] 27mmol zinc acetate dihydrate was dissolved in 50mL ultrapure water, 18mmol 4,4'-bipyridine and 18mmol malic acid were dissolved in 75mL methanol, and after being fully dissolved, the two mixed solutions were stirred at room temperature for 1h to be fully mixed, and stirred and refluxed at 130°C for 44h. The obtained slurry was collected by suction filtration, and the obtained solid was dried at 60°C to obtain the Zn-bpy-DLmal powder sample.

[0057] Comparative Example 1

[0058] In this comparative example, a metal organic framework is prepared using fumaric acid as a ligand, and the preparation method comprises the following steps:

[0059] Dissolve 2.4mmol zinc acetate dihydrate in 5mL ultrapure water, 1.8mmol 4,4'-bipyridine and 1.8mmol fumaric acid in 5mL methanol, transfer the two mixed solutions to a polytetrafluoroethylene reactor after they are fully dissolved, stir at room temperature for 1h to fully mix, then put them in a 140℃ oven to react for 48h, and cool to room temperature 10h after the reaction. The obtained white powder sample is the Zn-bpy-fum powder sample. The actual picture is shown in Figure 4.

[0060] The carboxyl oxygen atoms and hydroxyl oxygen atoms on the malic acid ligands in the metal organic framework material are bonded to the metal zinc ions to form a regular 2D layered network structure. The adjacent 2D layered network structures are further bridged by 4,4'-bipyridine. After the malic acid and the zinc ion are connected by ionic bonds, the hexacoordinated zinc ion will produce a vacancy, and continue to link with the nitrogen atom in 4,4-bipyridine through coordination bonds to form a stable structure. The self-assembled assembly forms a regular, highly stable 3D rigid network framework with a dense cavity structure. The structure of the metal organic framework material Zn-bpy-DLmal is shown in the figure. Figure 5 As shown. The cavity size of the 3D rigid network framework is 0.85×0.6×0.62nm 3 The pore size connecting adjacent cavities is 0.3nm×0.39nm, and the pore capacity is 0.1~0.2cm 3 / g, porosity of 30-40%, specific surface area of ​​150-300m 2 / g.

[0061] The structure of the metal organic framework material Zn-bpy-fum in Comparative Example 1 is as follows Figure 6 As shown. The one-dimensional through-aperture size of the 3D flexible interpenetrating network framework is 0.3×0.42nm3 , pore capacity 0.05~0.1cm 3 / g, specific surface area is 100~200m 2 / g.

[0062] Figure 7 This is the X-ray diffraction diagram of the synthetic phase purity and organic solution immersion stability test of the Zn-bpy-DLmal material in Example 1 of the present invention. Figure 7 In a, Activated refers to the activation treatment of the Zn-bpy-DLmal material prepared in Example 1, As-synthesized refers to the Zn-bpy-DLmal material synthesized in Example 1, and Simulated refers to the XRD simulation of the obtained crystal structure information (cif file) using Materials Studio 2023 software. The Zn-bpy-DLmal material synthesized in Example 1 shows extremely high diffraction peak intensity, indicating high crystallinity and phase purity; at the same time, after being immersed in organic solution and aqueous solution for one week, as shown in Figure 7 As shown in b, there is basically no change in the X-ray diffraction peak value and peak position, which further verifies the stability of the material in organic solution and water stability.

[0063] It should be noted that the specific activation treatment steps are: washing the Zn-bpy-DLmal material sample three times with a methanol solution, and drying it overnight at 60° C. under vacuum conditions for 12 hours.

[0064] Figure 8 This is a thermogravimetric curve of the Zn-bpy-DLmal material of Example 1 of the present invention. Figure 8 As shown, the Zn-bpy-DLmal material synthesized in Example 1 has an obvious weight loss at 400°C, indicating the collapse of the framework structure, and the thermal stability of the material is as high as 400°C.

[0065] When conducting gas adsorption tests, the Zn-bpy-DLmal and Zn-bpy-fum materials need to be activated to remove guest molecules in the materials. The activation method is the same as the above activation steps.

[0066] Fig. 9 195K is the CO2 adsorption isotherm of the Zn-bpy-DLmal material of Example 1 of the present invention. Fig. 9 As shown in Figure 1, the specific surface area of ​​the Zn-bpy-DLmal material synthesized in Example 1 was calculated by CO2 adsorption at 195K to be 162.7 m 2 / g, pore capacity is 0.116cm 3 / g.

[0067] Fig.10The CO2 adsorption isotherm at 195°C for the Zn-bpy-fum material in Comparative Example 1 of the present invention. Fig.10 As shown in the figure, the specific surface area of ​​the Zn-bpy-fum material synthesized in Comparative Example 1 was calculated by CO2 adsorption at 195K to be 145.1 m 2 / g, pore capacity is 0.089cm 3 / g.

[0068] Fig.11 is the adsorption isotherm of acetylene and carbon dioxide of the Zn-bpy-DLmal material of Example 1 of the present invention at 298K, such as Fig.11 As shown, at 298K, the adsorption amounts of acetylene and carbon dioxide by the Zn-bpy-DLmal material synthesized in Example 1 are 3.1 mmol / g and 1.9 mmol / g, respectively.

[0069] Fig.12 The adsorption isotherms of acetylene and carbon dioxide of the Zn-bpy-fum material of Comparative Example 1 of the present invention at 298K are as follows: Fig.12 As shown, under 298K conditions, the adsorption amounts of acetylene and carbon dioxide by the Zn-bpy-fum material synthesized in Comparative Example 1 are 1.9 mmol / g and 0.4 mmol / g, respectively, and there is an obvious "opening door phenomenon", which is not conducive to the separation of mixed gases.

[0070] Fig.13 The kinetic adsorption curve of acetylene and carbon dioxide adsorption over time of the Zn-bpy-DLmal material of Example 1 of the present invention at 298K (equilibrium pressure is 500mbar). Fig.13 As shown, acetylene and carbon dioxide both reached adsorption equilibrium at 10 min, but the adsorption amounts were quite different, which were 3.18 mmol / g and 1.95 mmol / g, respectively.

[0071] The metal organic framework material Zn-bpy-DLmal obtained in Example 1 was loaded into a fixed bed adsorption column with an inner diameter of 4.6 mm and a length of 20 cm. At 298K and 1 bar, a mixture of acetylene / carbon dioxide (50:50) flowed through the fixed bed adsorption column filled with the metal organic framework material Zn-bpy-DLmal at a fixed flow rate of 2.0, 5.0 or 10.0 mL / min. The carbon dioxide component preferentially penetrated the bed layer, and high-purity carbon dioxide gas (>99.9%) was obtained at the tail end of the adsorption column. When the adsorption column was completely penetrated, adsorption was stopped. Under the condition of 100°C, the adsorption column was purged with helium to achieve cyclic regeneration, and high-purity acetylene gas (≥99%) was obtained during the regeneration process; or at 100°C, a vacuum pump was used for desorption and regeneration, and the vacuum degree was 0.05 bar.

[0072] Fig.14 The dynamic penetration curves of the Zn-bpy-DLmal material prepared in Example 1 of the present invention at 298K with three different flow rates of 2.0mL / min, 5.0mL / min, and 10.0mL / min and a volume ratio of 1:1 for acetylene / carbon dioxide mixed gas components are shown in FIG. Fig.14 As shown, acetylene and carbon dioxide have obvious separation working ranges, and exhibit excellent separation performance at all three flow rates.

[0073] Fig.15 The cyclic dynamic breakthrough curve of the Zn-bpy-DLmal material prepared in Example 1 of the present invention under the condition of 298K with a volume ratio of 1:1 acetylene / carbon dioxide mixed gas components at a flow rate of 2.0mL / min is as follows: Fig.11 As shown, in the five cycles, the breakthrough time interval of acetylene carbon dioxide did not decrease significantly, maintaining good cycle stability.

[0074] Fig.16 The acetylene desorption process curve of the Zn-bpy-DLmal material prepared in Example 1 of the present invention after dynamic penetration of acetylene / carbon dioxide mixed gas components with a volume ratio of 1:1 at a flow rate of 2.0 mL / min at 298K is as follows: Fig.16 As shown, when purging and decomposing with 10 mL / min of helium, carbon dioxide is first purged at about 11.3 min / g, and then acetylene product with a purity of ≥99% is obtained.

[0075] Fig.17 The adsorption isotherms of acetylene and carbon dioxide for the kilogram-scale synthetic sample of the Zn-bpy-DLmal material prepared in Example 3 of the present invention at 298K are as follows: Fig.17 As shown, the adsorption capacity of the Zn-bpy-DLmal material synthesized by scale-up for acetylene and carbon dioxide did not weaken significantly.

[0076] Fig.18 The dynamic penetration curve of the kilogram-scale synthetic sample of the Zn-bpy-DLmal material prepared in Example 3 of the present invention under the condition of 298K with a volume ratio of 1:1 acetylene / carbon dioxide mixed gas components at a flow rate of 2.0mL / min is as follows: Fig.18 As shown, the Zn-bpy-DLmal material synthesized by enlargement has a distinct separation working range for acetylene and carbon dioxide, and maintains excellent separation performance.

[0077] The metal organic framework material Zn-bpy-fum obtained in Comparative Example 1 was loaded into a fixed bed adsorption column with an inner diameter of 4.6 mm and a length of 20 cm. At 298K and 1 bar, a mixture of acetylene / carbon dioxide (50:50) flowed through the fixed bed adsorption column filled with the metal organic framework material Zn-bpy-fum at a fixed flow rate of 2.0 mL / min. The carbon dioxide component preferentially penetrated the bed layer, and high-purity carbon dioxide gas (>99%) was obtained at the tail end of the adsorption column. When the adsorption column was completely penetrated, adsorption was stopped. Under 100°C, the adsorption column was purged with helium to achieve cyclic regeneration, and acetylene gas (≥90%) was obtained during the regeneration process; or at 100°C, it was desorbed and regenerated with a vacuum pump, and the vacuum degree was 0.05 bar.

[0078] Fig.19 The dynamic penetration curve of the Zn-bpy-fum material in Comparative Example 1 of the present invention at 298K with a flow rate of 2.0 mL / min and a volume ratio of 1:1 for acetylene / carbon dioxide mixed gas components is shown in FIG. Fig.19 As shown, acetylene and carbon dioxide have a relatively short separation working interval, and the purity of the obtained gas is low.

[0079] Fig. 20 The acetylene desorption process curve of the acetylene / carbon dioxide mixed gas component with a volume ratio of 1:1 at a flow rate of 2.0 mL / min after dynamic penetration of the Zn-bpy-fum material in Comparative Example 1 of the present invention is as follows: Fig. 20 As shown in the figure, when 5 mL / min of helium is used for purging and analysis, carbon dioxide is first purged at about 10.2 min / g, and then acetylene products with a purity of ≥90% are obtained, which is lower than the product concentration of Zn-bpy-DLmal prepared in Example 1 under the same conditions. This is because the Zn-bpy-fum material has a flexible structure with double interpenetration, which will produce obvious co-adsorption phenomenon in the dynamic separation process, thereby affecting the concentration of the obtained product.

[0080] It should be noted that the preparation method described in Example 1 synthesizes a crystalline sample, and the preparation methods of Examples 2 and 3 synthesize powder samples. The performance parameters of the crystalline sample or the powder sample are relatively close, and the performance difference can be basically ignored.

[0081] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a metal organic framework material, characterized in that: The following steps are involved: Using water and methanol as solvents, 4,4'-bipyridine and malic acid as organic ligands, and adding a zinc source, the reaction is carried out. During the reaction, the oxygen atoms on the malic acid are bonded to the zinc ions on the zinc source to form a 2D layered network structure. The 2D layered network structures are bridged by 4,4'-bipyridine to form a 3D rigid network framework. After the reaction is completed, a metal-organic framework material is prepared.

2. The method for preparing a metal organic framework material according to claim 1, characterized in that: The molar ratio of the zinc source to 4,4'-bipyridine is 4 to 5:

3.

3. The method for preparing a metal organic framework material according to claim 1, characterized in that: The molar ratio of the zinc source to malic acid is 4 to 5:

3.

4. The method for preparing a metal organic framework material according to claim 1, characterized in that: The reaction temperature is 120°C to 150°C, and the reaction time is 40h to 48h.

5. The method for preparing a metal organic framework material according to claim 1, characterized in that: The volume ratio of water to methanol is 1:1-2, and the ratio of zinc source to water is 2.4mmol-3mmol:5ml.

6. A metal organic framework material prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the metal organic framework material according to claim 6 as an adsorbent, characterized in that: The metal organic framework material is used as an adsorbent and is brought into contact with a gas mixture containing acetylene and carbon dioxide for adsorption separation.

8. The use of the metal organic framework material as an adsorbent according to claim 7, characterized in that: In the gas mixture, the volume percentage of acetylene is 1% to 99%, and the rest is carbon dioxide, which is 100% in total.

9. The use of the metal organic framework material as an adsorbent according to claim 7, characterized in that: The temperature of adsorption separation is -50°C to 100°C, and the adsorption pressure is 0 bar to 10 bar.

10. The use of the metal organic framework material as an adsorbent according to claim 7, characterized in that: The contact mode is any one of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption.

Citation Information

Patent Citations

  • Hierarchical heterogeneous covalent organic framework material, preparation method and application thereof

    CN112705179A

  • Sodium-ion battery diaphragm as well as preparation method and application thereof

    CN117673653A

  • Method for adsorbing and separating propylene and propane

    CN117776852A

Cited By

  • Preparation method of Ni-DLMB type MOF film

    CN120325088A

  • A method for preparing a Ni-DLMB type MOF membrane

    CN120325088B